Th The role of sports activities in teaching the blind about quality of life from the perspective of faculty members at the Faculty of Physical Education at Tishreen University )A field study( - أحمد, سارة; بلال محمود; ماهر نصر; ريم سلمان (Latakia University Journal -Medical Sciences Series, 2024)
The research aims to know the role of sports activities in educating blind people about quality of life, as viewed by faculty members at the Faculty of Physical Education at Tishreen University. It also aims to study the differences in the opinions of faculty members at the Faculty of Physical Education at Tishreen University regarding the role of sports activities in teaching the blind about quality of life according to the variables of the study (gender, academic rank). The researcher used the descriptive approach in the style of a comprehensive survey, and a questionnaire was constructed that consisted of (36) statements covering the aspects of the research. The research sample included (19) faculty members from the Faculty of Physical Education, Tishreen University, and was drawn using a comprehensive inventory. After study and analysis, the results were reached. next: -1 There are no statistically significant differences at the significance level (= 0.05a) in the opinions of faculty members at the Faculty of Physical Education at Tishreen University regarding the role of sports activities in educating the blind about quality of life, due to the gender variable. -2 There are statistically significant differences at the significance level (= 0.05a) in the opinions of faculty members at the Faculty of Physical Education at Tishreen University regarding the role of sports activities in educating the blind about quality of life, due to the academic rank variable. -3 One of the research proposals is rehabilitation for the blind to improve functional ability through sports activities to teach them quality of life and its reflection on the quality of life and psychological and social status.